Kinetic and mechanistic investigation of the ring-opening polymerization of l-lactide initiated by nBu3SnOnBu using 1H-NMR - Limwanich W. (2017)
© 2016, Akadémiai Kiadó, Budapest, Hungary. The kinetics of the ring-opening polymerization (ROP) of l-lactide (LL) initiated by tri-n-butyltin n-butoxide (nBu 3 SnOnBu) was investigated by proton nuclear magnetic resonance spectroscopy ( 1 H-NMR). The kinetic parameters such as the rate constant (k) and the activation energy (E a ) were determined. The values of k increased with increasing temperature and initiator concentration. The E a values determined from the ROP of LL initiated by 1.0, 1.5 and 2.0 mol% of nBu 3 SnOnBu were 95.9, 87.8 and 72.4 kJ/mol. The molecular weight of poly(l-lactide) (PLL) was successfully controlled by adjusting nBu 3 SnOnBu concentration. Furthermore, the number average molecular weight (M¯ n ) of these polymers was in the range of 1.1 × 10 4 –3.2 × 10 4 with molecular weight distribution of 1.4–1.9 and the molecular weight of PLL was higher than poly(ε-caprolactone) under identical synthesis conditions. Furthermore, the molecular weight of the synthesized polymers was lower than the theoretical values (M¯ n (cal)) indicating the occurrence of transesterification.